Unethical Pro-organisational Behaviour: Concepts, Motives and Unintended Consequences. (December 2019) - Hosain, Md Sajjad
With the increase in diversity in the nature of job and human behavioural complicatedness, a new common phenomenon has emerged in workplaces termed as unethical pro-organisational behaviour which has succeeded to attract the attention of behavioural academicians. As a fairly new concept, there is lack of adequate research in this area of organisational psychology. The article mainly aims at discussing the motives for and the consequences of such behaviours with the help of existing literature available. The author argues that the organisations should express their intentions and actions in order to reduce such behavioural tendencies. The article is expected to help further research in this area by summarising the highlights from existing works available.